2023
DOI: 10.1021/acs.jproteome.2c00441
|View full text |Cite
|
Sign up to set email alerts
|

prolfqua: A Comprehensive R-Package for Proteomics Differential Expression Analysis

Abstract: Mass spectrometry is widely used for quantitative proteomics studies, relative protein quantification, and differential expression analysis of proteins. There is a large variety of quantification software and analysis tools. Nevertheless, there is a need for a modular, easy-to-use application programming interface in R that transparently supports a variety of well principled statistical procedures to make applying them to proteomics data, comparing and understanding their differences easy. The prolfqua package… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…We have shown that at the peptide and protein level, for DIA, label-free DDA and TMT experiments, no imputation generally works, as well as the most commonly used imputation methods. Our results are in line with Wolski et al, who suggest that statistical models of differential expression that do not impute, but rather explicitly model missingness, tend to outperform traditional models …”
Section: Discussionsupporting
confidence: 92%
“…We have shown that at the peptide and protein level, for DIA, label-free DDA and TMT experiments, no imputation generally works, as well as the most commonly used imputation methods. Our results are in line with Wolski et al, who suggest that statistical models of differential expression that do not impute, but rather explicitly model missingness, tend to outperform traditional models …”
Section: Discussionsupporting
confidence: 92%
“…The R package prolfqua 63 was used to analyse differential expression and to determine group differences, confidence intervals and false discovery rates for all quantifiable proteins. Starting with the precursor abundances reported by DIA-NN, we determined protein abundances using the Tukeys-median polish.…”
Section: Methodsmentioning
confidence: 99%
“…prolfqua 23 ( ) integrates the basic steps of a differential expression analysis workflow: quality control, data normalization, protein aggregation, statistical modeling, hypothesis testing, and sample size estimation. The modular design of prolfqua enables users to select the optimal differential expression analysis algorithm.…”
Section: R-packages For Statistical Analysis Of Quantitative Lfq-base...mentioning
confidence: 99%
“…Previous works have mainly focused on evaluating the software that performs peptide identification, protein inference, and the generation of protein intensity tables. ,, We first briefly describe the main packages and tools that enable the statistical analysis of LFQ data sets from peptide or protein intensity data. While multiple packages and tools are available for statistical analysis of these data, we selected some of the most relevant ones and novel implementations including MSstats, Perseus, Proteus, prolfqua, ProVision, LFQ-Analyst, Eatomics, ProStaR, and msqrob2. Finally, we used three different data setsUPS spiked data set, large-scale mix data set and toxicology data setto evaluate the performance of each tool and discuss some of the advantages and disadvantages of their use with different types of data sets.…”
Section: Introductionmentioning
confidence: 99%